2019
DOI: 10.1371/journal.pgen.1008417
|View full text |Cite
|
Sign up to set email alerts
|

European Roma groups show complex West Eurasian admixture footprints and a common South Asian genetic origin

Abstract: The Roma population is the largest transnational ethnic minority in Europe, characterized by a linguistic, cultural and historical heterogeneity. Comparative linguistics and genetic studies have placed the origin of European Roma in the Northwest of India. After their migration across Persia, they entered into the Balkan Peninsula, from where they spread into Europe, arriving in the Iberian Peninsula in the 15th century. Their particular demographic history has genetic implications linked to rare and common di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 56 publications
4
72
1
Order By: Relevance
“…Applying the f4 ratio estimation, we estimated this admixture to be between 48-54% (Supplementary Table 6). Roma groups from the Balkan Peninsula and Central Europe tend to have lower West Eurasian ancestry than other Roma groups 16,22 .…”
Section: Ancestry Of Roma People From Romania To Explore the Geneticmentioning
confidence: 86%
See 2 more Smart Citations
“…Applying the f4 ratio estimation, we estimated this admixture to be between 48-54% (Supplementary Table 6). Roma groups from the Balkan Peninsula and Central Europe tend to have lower West Eurasian ancestry than other Roma groups 16,22 .…”
Section: Ancestry Of Roma People From Romania To Explore the Geneticmentioning
confidence: 86%
“…It has been suggested that the West Eurasian ancestry present within India, and mainly in the North, increases the genetic similarity of the Roma with other European populations 3,14 . This, together with the influx of European migrants into a population with small effective size and the high genetic drift of the Roma subgroups, make the Roma more genetically similar to European than to South Asian populations 16 .…”
Section: Ancestry Of Roma People From Romania To Explore the Geneticmentioning
confidence: 99%
See 1 more Smart Citation
“…They began their migration westwards between the 6th to 10th century, with groups settling along the way, finally entering Europe in the 12th century. Roma communities across Europe and Central Asia gradually formed diverse endogamous sub-groupings, still retaining large parts of their language and culture [ 1 , 2 ]. In Europe alone they now number around 11 million, the vast majority living in Eastern and Central Europe ( Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Roma population is the largest transnational ethnic minority in Europe, characterized by linguistic [ 1 , 2 , 3 ], cultural [ 4 , 5 ] and historical heterogeneity [ 6 , 7 , 8 ]. Roma are thus not a single, homogeneous group of people [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%